EFEKTIFITAS KOMPOS LIMBAH MEDIA TANAM JAMUR TIRAM SEBAGAI PUPUK ORGANIK PADA BUDIDAYA BAWANG MERAH DI TANAH ULTISOL - Agus Mulyadi Purnawanto; Bambang Nugroho (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2015)
Land resources is one of the critical success factors of farming systems. One of the potential land is Ultisol with an area of 47.5 million hectares, but has low soil fertility. So it needs to be studied regarding the use of compost of oyster mushroom growing media waste inUltisol in onion cultivation. The research is based on a randomized block design with eight replications. Factors studied were oyster mushroom growing media waste consists of three levels ie without waste (L0), given the fresh waste as much as 20 t ha-1 (L1) and given compost waste as much as 20 t ha-1 (L2).The results showed that giving zeolite as much as 1 t ha-1 in Ultisol did not significantly affect onion crop, whereas giving of waste oyster mushroom growing medium as much as 20 t ha-1 significantly affected the onion crop, although there is no difference between waste freshor composted. There is no interaction between the zeolite and the giving waste oyster mushroom growing media on growth and yield of onion.Keywords: compost, waste, oyster mushrooms, onion